Persistence of informality in a developing conuntry (2012)
Informality is a common phenomenon in developing countries and an unusual one in industrialized countries. The persistence of informal employment is indicative of the impossibility of moving out of this status for a certain period of time. Using pseudo panel data, empirical evidence is presented to show that this phenomenon occurs in a developing country like Colombia where education helps mitigate said persistent occurrence. The authors also present evidence that a minimum salary increase does not only result in increased informality, but also increases the persistence of informality. This kind of evidence can be used for discussing the persistence of informality in other developing countries.